(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
This is an essay written by me when I was yet in my younger years, since then I have simplified the same in several other papers. It intrigues me in my old age now to behold my state of mind in those days long ago. This essay is a review into the fundamentals of the laws of motion, showing the cause to gravitational force to come about in the same laws by which it is governed. We then may be intrigued to behold how this gravitational force finds its birth by way of “movement into movement upon a twofold inertia". And while it may seem acceptable to us that objects are attracted unto one another proportional to their masses, the evidence in both law and experiment are stacked against it. Hence, the property of mass that gives rise to its force of attraction is found to be “its own movement".